Rediscovery of Traditional Ecological Knowledge as Adaptive Management - Berkes, Fikret; Colding, Johan; Folke, Carl (Ecological Applications, 2000)
Indigenous groups offer alternative knowledge and perspectives based on their own locally developed practices of resource use. We surveyed the international literature to focus on the role of Traditional Ecological Knowledge in monitoring, responding to, and managing ecosystem processes and functions, with special attention to ecological resilience. Case studies revealed that there exists a diversity of local or traditional practices for ecosystem management. These include multiple species management, resource rotation, succession management, landscape patchiness management, and other ways of responding to and managing pulses and ecological surprises. Social mechanisms behind these traditional practices include a number of adaptations for the generation, accumulation, and transmission of knowledge; the use of local institutions to provide leaders/stewards and rules for social regulation; mechanisms for cultural internalization of traditional practices; and the development of appropriate world views and cultural values. Some traditional knowledge and management systems were characterized by the use of local ecological knowledge to interpret and respond to feedbacks from the environment to guide the direction of resource management. These traditional systems had certain similarities to adaptive management with its emphasis on feedback learning, and its treatment of uncertainty and unpredictability intrinsic to all ecosystems.
Keywords: Adaptive Management; Resource management; Social learning; Traditional Ecological Knowledge; human ecology; resilience

From Users and Choosers to Makers and Shapers. Repositioning Participation in Social Policy - Cornwall, Andrea; Gaventa, John (IDS Bulletin, 2000)

Evaluating the ‘logical framework approach’ towards learning-oriented development evaluation - Gasper, Des (Public Administration and Development, 2000)
The logical framework approach has spread enormously, including increasingly to stages of review and evaluation. Yet it has had little systematic evaluation itself. Survey of available materials indicates several recurrent failings, some less easily countered than others. In particular: focus on achievement of intended effects by intended routes makes logframes a very limiting tool in evaluation; an assumption of consensual project objectives often becomes problematic in public and inter-organizational projects; and automatic choice of an audit form of accountability as the priority in evaluations can be at the expense of evaluation as learning.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/1099-162X%28200002%2920%3A1%3C17%3A%3AAID-PAD89%3E3.0.CO%3B2-5